STRATEGI PENGEMBANGAN SENI LUKIS WAYANG KACA NAGASEPAHA SEBAGAI DAYA TARIK WISATA BERBASIS EKONOMI KREATIF - Putu Agus Wirawan; Ida Bagus Gede Paramita; Made Novita Dwi Lestari (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
Nagasepaha glass painting is one of the differentiations owned by Nagasepaha village, because it has a uniqueness of the object. Having a typical painting technique with a decorative style and naturalism also painting in a reverse style. The development era of globalization generate competition for artists to continue to create innovative and adaptive works. However, there are problems from artists with lack of comprehension about digital marketing, sales, to marketing. Until there needs to be a development of Nagasepaha glass puppet painting to be more innovative and adaptive. This study aimed at : 1) To finding out the creative process of Nagasepaha glass painting, (2) To identify potential creative economy-based tourism attractions from Nagasepaha glass painting, (3) To analyze the development strategy of Nagasepaha glass painting based on creative economy. This research uses a qualitative type of research with a case study approach. Data collection through literature study, observation, interviews, and documentation. Using the SWOT analysis method. The result of this research is that the creative process of Nagasepaha glass painting is quite developed, because there are encouraging factors, namely internal and external factors. Until there are potentials contained with the existence of glass paintings starting from the welfare of artists, communities and Nagasepaha village.